2014
DOI: 10.3390/toxins6092787
|View full text |Cite
|
Sign up to set email alerts
|

Toxin ζ Reversible Induces Dormancy and Reduces the UDP-N-Acetylglucosamine Pool as One of the Protective Responses to Cope with Stress

Abstract: Toxins of the ζ/PezT family, found in the genome of major human pathogens, phosphorylate the peptidoglycan precursor uridine diphosphate-N-acetylglucosamine (UNAG) leading to unreactive UNAG-3P. Transient over-expression of a PezT variant impairs cell wall biosynthesis and triggers autolysis in Escherichia coli. Conversely, physiological levels of ζ reversibly induce dormancy produce a sub-fraction of membrane-compromised cells, and a minor subpopulation of Bacillus subtilis cells become tolerant of toxin acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Therefore, the inhibitory effect of SezT in this study should be interpreted as a consequence of triggering cell death rather than cell stasis. Previously, it was reported that physiological levels of Zeta toxin reversibly induce dormancy in B. subtilis and E. coli cells (Tabone et al ., 2014a,b). Conversely, upon massive overexpression, the PezT toxin triggers autolysis with few intact cells with an ovoid morphology (Mutschler et al ., ), but such massive autolysis was not observed upon Zeta overexpression (Zielenkiewicz and Ceglowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibitory effect of SezT in this study should be interpreted as a consequence of triggering cell death rather than cell stasis. Previously, it was reported that physiological levels of Zeta toxin reversibly induce dormancy in B. subtilis and E. coli cells (Tabone et al ., 2014a,b). Conversely, upon massive overexpression, the PezT toxin triggers autolysis with few intact cells with an ovoid morphology (Mutschler et al ., ), but such massive autolysis was not observed upon Zeta overexpression (Zielenkiewicz and Ceglowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ζ functions to inhibit bacterial cell wall synthesis (Mutschler and Meinhart, 2011 ; Mutschler et al, 2011 ). However, a recent paper reported that expression of ζ only reduced the UNAG pool and did not totally deplete it with transient expression of ζ (120 min) reversibly inducing a dormant state that was subsequently rescued by ε expression (Lioy et al, 2012 ; Tabone et al, 2014 ). It was proposed that ζ expression induces diverse responses to cope with stress with reduction in the UNAG levels as one of these responses rather than triggering a latent suicide program by depleting the UNAG pool (Tabone et al, 2014 ).…”
Section: Tripartite Type II Ta Locimentioning
confidence: 99%
“…Moreover, two different mechanisms of action for the epsilon/zeta systems have been described so far. In the first one, the cell wall formation is affected through phosphorylation of the UDP-N-acetylglucosamine (UNAG) on its 3’-hydroxyl group [ 20 , 22 ], causing a reversible growth arrest [ 23 , 24 ]. The second mechanism of action implies the phosphorylation of nicotinamide adenine dinucleotide (NAD) or its precursor, nicotinic acid adenine dinucleotide (NAAD), at the adenosine 3’-hydroxil group, affecting NAD/NAAD-dependent pathways [ 25 ].…”
Section: Introductionmentioning
confidence: 99%